Conversational AI for farmers - R. Venkata Sai Gowtham; K. Venkata Ramana (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This paper presents a web-based conversational AI system designed to assist farmers with agricultural queries. Developed using the Flask framework, the application incorporates user authentication and a chatbot powered by Google’s Gemini 1.5 Pro model. Users can register and log in, with credentials securely stored in a MySQL database. The system features intuitive web interfaces for navigation and a dedicated chatbot page, where farmers submit queries via a JSON-based API endpoint. Responses are formatted for clarity, ensuring relevance to farming contexts. The proposed solution enhances accessibility to real-time agricultural guidance, demonstrating the potential of conversational AI to support farming communities effectively.